1989
DOI: 10.1111/j.1365-2125.1989.tb03445.x
|View full text |Cite
|
Sign up to set email alerts
|

A stereochemical investigation of the cytotoxicity of mianserin metabolites in vitro.

Abstract: 1. The metabolism of the enantiomers of mianserin to stable, chemically reactive and cytotoxic metabolites by human liver microsomes has been investigated in vitro. 2. Both enantiomers were metabolised to three major oxidation products: 8‐hydroxymianserin, desmethylmianserin and mianserin 2‐oxide. Hydroxylation occurred more readily with the S‐ enantiomer, whereas desmethylmianserin was always the major metabolite of the R‐enantiomer. 3. The generation of chemically reactive metabolites exhibited a marginal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Circumstantial evidence has been presented, which links toxicity to the P450-mediated bioactivation of the parent compound 97 and its primary urinary metabolites , 8-hydroxymianserin ( 98 ), and N -desmethyl-mianserin ( 99 ) to the corresponding reactive iminium ions 100 – 102 in HLM (Scheme ). The detection of cyanide adduct(s) , in incubations of 97 in HLM containing NADPH and cyanide is consistent with these observations. Studies with radiolabeled mianserin and its metabolites also resulted in the NADPH-dependent, irreversible incorporation of radiolabel in microsomal protein and cytotoxicity toward human mononuclear leukocytes included in the microsomal incubation. , A reactive iminium species 103 and its corresponding cyanide adduct 104 have also been detected in incubations of mianserin human neutrophils and in incubations with horseradish peroxidase/H 2 O 2 .…”
Section: Adverse Drug Reactions Linked To Iminium/aldehyde Formationsupporting
confidence: 79%
“…Circumstantial evidence has been presented, which links toxicity to the P450-mediated bioactivation of the parent compound 97 and its primary urinary metabolites , 8-hydroxymianserin ( 98 ), and N -desmethyl-mianserin ( 99 ) to the corresponding reactive iminium ions 100 – 102 in HLM (Scheme ). The detection of cyanide adduct(s) , in incubations of 97 in HLM containing NADPH and cyanide is consistent with these observations. Studies with radiolabeled mianserin and its metabolites also resulted in the NADPH-dependent, irreversible incorporation of radiolabel in microsomal protein and cytotoxicity toward human mononuclear leukocytes included in the microsomal incubation. , A reactive iminium species 103 and its corresponding cyanide adduct 104 have also been detected in incubations of mianserin human neutrophils and in incubations with horseradish peroxidase/H 2 O 2 .…”
Section: Adverse Drug Reactions Linked To Iminium/aldehyde Formationsupporting
confidence: 79%
“…1). However, in agreement with previous studies (Riley et al 1989), a stereochemical difference was observed with NADPH-dependent cytotoxicity being greater with (-)-mianserin than with (+)-mianserin ( Fig. 1); (+)mianserin, in contrast, showed direct cytotoxicity at high concentrations.…”
Section: Resultssupporting
confidence: 92%
“…Indeed, aromatic oxidation in human liver microsomes occurred more readily with the (S)-enantiomer, while N-demethylation was the major route for the (R)-enantiomer. At low drug concentrations, cytotoxicity toward human mononuclear leukocytes was due to (R)-mianserin more than to (S)-mianserin, and showed a significant correlation with N-demethylation (RILEY et al 1989). Thus for mianserin toxicity was associated with N-demethylation rather than aromatic oxidation, while the reverse appeared true for disopyramide.…”
Section: Disopyramide (Fig 2a) Is a Chiral Antiarrhythmic Agent Markmentioning
confidence: 85%